Analisis Penyebab Eksploitasi Anak di Bawah Umur Pada Saat Pandemi Covid-19 - Nasrul Fuad Erfansyah; Taseman Taseman; Safaruddin Safaruddin; Abd Malik Dachlan; Amirah Yasmin; Dinda Dwi Pangestu Ningrum; Juhaeni Juhaeni (JECED : Journal of Early Childhood Education and Development, 2021)
A child is the successor of a nation that must obtain protection in his life by the nation and the state, government, society, and parents, the child must also obtain rights that are upheld as a human being. The purpose of this research is to find out how forms of child exploitation and the factors that cause the emergence of cases of exploitation of minors during the Covid-19 pandemic. This research uses qualitative descriptive research and library research. The result of this study that there are three forms of child exploitation, namely physical exploitation, social exploitation and sexual exploitation. For factors that cause high cases of exploitation of minors during the pandemic, namely, low family economy, low parental education, child abuse and fractures of the parents' households, and environmental influences and online learning. Perpetrators of child exploitation cases do not get a deterrent effect due to the lack of swiftness of the government to make regulations and penalties that provide a deterrent effect for perpetrators. Thus the importance of awareness of parents, society and the importance of law enforcement to protect minors in order to avoid the crimes of exploitation that are currently increasingly happening.